Evaluasi Keberhasilan Penerapan Inovasi Suroboyo (Inovboyo) Dalam Meningkatkan Kesejahteraan Dan Daya Saing Daerah - Efil, Alaya Azzahra; Alfitri, Adelia Rizki; Aulia, Gracika Anggun; Nafi’ah, Binti Azizatun (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
This research discusses the evaluation of the Suroboyo Innovation Program (Inovboyo) organized by the Surabaya City Government to encourage community participation in creating regional innovations. The introduction highlights the importance of regional innovation as an effort to improve competitiveness and community welfare, as well as the challenges of participation that had declined in 2023. The research uses a descriptive qualitative method with data collection through interviews, observation, and document analysis, as well as Miles and Huberman's interactive analysis technique to gain an in-depth understanding of the inhibiting and supporting factors of community participation. Theories of community participation and public policy served as the basis for the analysis, with a CIPP (Context, Input, Process, Product) evaluation approach to assess program implementation and impact. The results showed that the main obstacles were limited understanding of the benefits of the program and the affordability of information, especially for people who were not familiar with digital technology. After improving the promotion and education strategy, participation increased significantly in 2024. The research conclusion confirms that the success of regional innovation programs is strongly influenced by adaptive communication strategies, massive socialization, and adequate digital infrastructure support. Recommendations are given that local governments continue to develop technology-based promotion strategies and strengthen collaboration with the local government.